2019
DOI: 10.1038/s41419-019-2123-y
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC01111 suppresses pancreatic cancer aggressiveness by regulating DUSP1 expression via microRNA-3924

Abstract: Dysfunction in long noncoding RNAs (lncRNAs) is reported to participate in the initiation and progression of human cancer; however, the biological functions and molecular mechanisms through which lncRNAs affect pancreatic cancer (PC) are largely unknown. Here, we report a novel lncRNA, LINC01111, that is clearly downregulated in PC tissues and plasma of PC patients and acts as a tumor suppressor. We found that the LINC01111 level was negatively correlated with the TNM stage but positively correlated with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…CCK-8 assay was applied to determine cellular proliferative ability as described previously. 29 At 24 h posttransfection, preparation of cell suspension was performed, and cell concentration was adjusted to 2 × 10 3 cells/mL. In total, 100 μL of the cell suspension was inoculated into wells of 96-well plates.…”
Section: Cell Counting Kit-8 (Cck-8) Assaymentioning
confidence: 99%
“…CCK-8 assay was applied to determine cellular proliferative ability as described previously. 29 At 24 h posttransfection, preparation of cell suspension was performed, and cell concentration was adjusted to 2 × 10 3 cells/mL. In total, 100 μL of the cell suspension was inoculated into wells of 96-well plates.…”
Section: Cell Counting Kit-8 (Cck-8) Assaymentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) exert an essential role in the occurrence and progression of tumors [ 3 , 4 ], mainly in cancer proliferation, metastasis, and other biological functions associated with tumorigenesis [ 5 , 6 ]. In PC, abnormal expression and dysfunction of lncRNAs are shown to be associated with rapid progression of cancer and distant metastasis [ 7 , 8 ]. A large number of studies have shown that lncRNA can participate in the regulation of various biological functions of tumors such as epigenetics, post-transcriptional regulation, genomic stability, and ceRNA regulation mechanism [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA LINC01111 is signi cantly downregulated in PC tissues and positively correlated with the survival of PC patients. LINC01111 sequesters miR-3924 to upregulate DUSP1 and inactivate the SAPK/JNK signaling pathway, thus suppressing PC tumorigenesis and metastasis (10). Tumor suppressor long noncoding RNA on chromosome 8p12 (termed TSLNC8) is a newly identi ed lncRNA.…”
Section: Introductionmentioning
confidence: 99%